THE ROLE OF GREEN SUKUK IN FINANCING RENEWABLE ENERGY PROJECTS IN INDONESIA: A LEGAL AND FINANCIAL FRAMEWORK ANALYSIS - Indah Dwiprigitaningtias; Mona Al Johani; Omar Ahmad (Yayasan Adra Karima Hubbi, 2025)
The increasing global demand for sustainable energy has positioned Green Sukuk as an innovative Islamic financial instrument to support renewable energy development while adhering to Sharia principles. Indonesia, as the largest issuer of sovereign Green Sukuk among Muslim-majority countries, demonstrates significant potential in aligning environmental sustainability with Islamic finance. This study aims to analyze the legal and financial frameworks governing Green Sukuk issuance in Indonesia and evaluate its effectiveness in financing renewable energy projects. A qualitative-descriptive method was employed using a doctrinal legal approach combined with case study analysis of Indonesia’s Green Sukuk programs between 2018 and 2023. The study examines regulatory documents, Ministry of Finance reports, and project financing data to assess compliance with both Sharia standards and environmental governance frameworks. The findings reveal that Green Sukuk has successfully mobilized capital for renewable energy and sustainable infrastructure, particularly in solar, geothermal, and hydropower projects. However, challenges persist regarding project selection transparency, verification standards, and the integration of international green finance taxonomy. The research concludes that strengthening the legal architecture, enhancing cross-sectoral governance, and developing standardized Green Sukuk evaluation mechanisms are essential to maximize its role in achieving Indonesia’s energy transition and sustainability goals.